Oral processing of meat-flavour textured soy proteins – Part II: Influence on taste compounds release and sensory perception - Conti, Ana Carolina [UNESP]; Septier, Chantal; Gourrat, Karine; Labouré, Hélène; Salles, Christian (Elsevier, 2025)
The study of food oral processing is crucial for understanding the release of volatile and nonvolatile compounds and sensory perception during mastication. Thus, we studied the effects of oral processing on sensory perception and compound release of meat-flavoured textured soy proteins (FTSPs). FTSPs were prepared by extrusion of soy protein concentrate with thiamine under three conditions: (1) low moisture/high temperature (30 % moisture, 180 °C), (2) intermediate conditions (34 % moisture, 160 °C), and (3) high moisture/low temperature (38 % moisture, 140 °C). All formulations contained added salt (1.0 g/100 g) and monosodium glutamate (0.4 g/100 g), then split into two treatments after extrusion, one containing vegetable oil (7.0 g/100 g), and one without. Sensory evaluations were conducted to assess salty taste, umami taste, and meat aroma, while sodium and glutamic acid release into saliva were analysed by HPLC. The odoriferous contributions of the volatile compounds in FTSPs obtained at 30 % M/180 °C and 38 % M/140 °C, both without vegetable oil, were evaluated by GC-O. Compared with the FTSPs obtained at 38 % moisture/140 °C, those obtained at 30 % moisture/180 °C stood out for their salty taste, umami taste, and meat aroma, as well as their greater quantity of volatile compounds and odoriferous contribution to meat aroma. Lower sodium and glutamic acid contents were found in saliva when vegetable oil was added, depending on extrusion conditions. Moreover, salty and umami intensities were negatively correlated with salt and glutamate release, respectively, but rather well correlated with meat perception, suggesting cross-modal perceptual interactions. In conclusion, the in-mouth breakdown of FTPS and the release of taste compounds depends on the extrusion conditions, presence or absence of vegetable oil, and chewing time, which affect flavour perception. A deeper study of the cross-modal interactions between meat aroma and salty taste is now necessary to better understand consumers' sensory experiences and to determine the most suitable processing and composition parameters for formulating foods that are both appreciated by consumers and are nutritionally balanced.